Association between des-acyl ghrelin at fasting and predictive index of muscle derangement, metabolic markers and eating disorders: a cross-sectional study in overweight and obese adults. (1st February 2022) - Perna, Simone; Spadaccini, Daniele; Gasparri, Clara; Peroni, Gabriella; Infantino, Vittoria; Iannello, Giancarlo; Riva, Antonella; Petrangolini, Giovanna; Alalwan, Tariq A.; Al-Thawadi, Salwa; Rondanelli, Mariangela
ABSTRACT: Background: This study aimed to analyse the impact of des-acyl and acyl ghrelin (AG) on a wide range of muscular and metabolic markers and in order to discover the possible relationships and interactions of des-acylated ghrelin (DAG) on eating disorders. Materials & Methods: A total of 88 subjects (64 women and 24 men, with a mean age of 43 years and a mean body mass index (BMI) of 30.20 ± 3.27 kg/m 2 ) were enrolled in the cross-sectional study. Results: The findings showed that for each unit of increase of free fat mass index (FFMI), levels of DAG decreased by −41.11 pg/mL ( p < 0.05). Moreover, similar associations with DAG were found for insulin ( β = −30.67; p < 0.001), leptin ( β = −0.64; p < 0.05), body weight ( β = −14.36; p < 0.001), and free fat mass (FFM) ( β = −30.67; p < 0.001). In addition, associations were found between DAG and resting energy expenditure (REE) ( β = −0.84; p = 0.05) and the binge eating scale (BES) in which a unit increase of the BES score Q3 (depression) correlated with a decrease of DAG levels ( β = −9.98; p = 0.08). Further, a unit increase of AG/DAG ratio correspond with an increase in body weight ( β = 12.20; p < 0.05), BMI ( β = 4.70; p < 0.05) and fat mass ( β = 7.30; p < 0.05). However, the AG/DAG ratio was not associated with FFMI ( β = 2.61; p = 0.165) and FFML/BMI ( β = −0, 064; p = 0.625). Conclusion: This study suggests that higher levels of DAG at fasting are indices of poor muscle mass, insulin resistance and depression.